"Because if we don't talk about it, how are we going to prevent it?": Lucidity, a narrative-based digital game about sexual violence. Issue 4 (3rd July 2016) - Gilliam, Melissa; Jagoda, Patrick; Jaworski, Erin; Hebert, Luciana E.; Lyman, Phoebe; Wilson, M. Claire
Abstract: This paper describes the development and evaluation of an interactive, narrative-based, multimedia game to promote learning and communication about sexual violence and health topics. High school-aged participants created the game concept in a three-week workshop, after which assets were assembled and refined by a university-based game design lab. The outcome, Lucidity, was a multimedia game with a nonlinear narrative that led to two different outcomes based on player decisions. The narrative followed the life of one character, an African American woman named Zaria who remembers and grapples with a sexual assault from her past. The player discovers parts of the story by reading comics, watching videos, navigating interactive websites and playing short videogames. The final evaluation consisted of gameplay, a post-game focus group and follow-up interviews. Twenty-four young people participated in three focus group discussions ( n  = 9, n  = 5, n  = 10); 23 participated in the follow-up interviews. Salient themes identified in the focus group discussions included: overall approval of the game, the acquisition of new knowledge and minimal past exposure to conversations or education about sexual violence. At follow-up, almost all ( n  = 22) had initiated a conversation about sexual violence with a parent, peer and/or teacher. Lucidity succeeded in engaging young people and facilitating communication with adults and peers regarding sexual violence and other sexual health topics. Ultimately, a game-based intervention such as this represents a feasible approach for introducing issues of sexual violence, with potential for future implementation in educational settings.